SOURCES AND METHODS OF FINANCING INVESTMENT ACTIVITIES IN THE REPUBLIC OF UZBEKISTAN (International journal of artificial intelligence, 2025)
This article examines various methods and sources of financing investment activities, emphasizing the necessity of utilizing both domestic capital and foreign loans, as well as direct investments and all related sources, to implement investment policies in the country.